The iron mistress - Wellman, Paul I. 1895-1966 (Doubleday, 1951)
Historical novel based on athe life of James Bowie.
Keywords: Bowie, James <d. 1836> -- Fiction; Sieges -- Fiction; Alamo (San Antonio, Tex.) -- Siege, 1836 -- Fiction; Texas -- Fiction; Biographical fiction; Western stories